2023
DOI: 10.31557/apjcp.2023.24.2.717
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Serum Level of IGF-1 and IGFBP-3 and the Risk of Breast Cancer among Women in the Gaza Strip

Abstract: Objective: The purpose of this research was to look at the relationship between insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) levels and the risk for breast cancer (BC) among women in the Gaza Strip. Methods: This case-control study, which included 334 participants (112 women with BC as cases, and 222 women without BC as control), was conducted between January 2021 and August 2022. Research data for the cases were gathered at the Oncology Departments of the Gaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additionally ( 13 ), integrated genetic mutations and demographic factors to predict breast cancer risk, highlighting the importance of considering metabolic pathways in risk assessment. These findings underscore the multifaceted nature of metabolism-related risk factors in breast cancer susceptibility ( 113 ) ( 9 ) and ( 13 ).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally ( 13 ), integrated genetic mutations and demographic factors to predict breast cancer risk, highlighting the importance of considering metabolic pathways in risk assessment. These findings underscore the multifaceted nature of metabolism-related risk factors in breast cancer susceptibility ( 113 ) ( 9 ) and ( 13 ).…”
Section: Resultsmentioning
confidence: 64%
“…Metabolism plays a crucial role in breast cancer risk, with various factors influencing susceptibility ( 113 ). found that high-density lipoprotein cholesterol (HDL-C) significantly affects breast cancer risk, suggesting a metabolic component to cancer development ( 9 ). identified associations between insulin-like growth factor 1 (IGF-1) levels and fasting blood glucose with breast cancer risk, emphasizing the complexity of metabolic factors.…”
Section: Resultsmentioning
confidence: 99%